The Role of Notary in Land Liberation Relation to PLTU Development for Public Interest - Dian Laras Sukma; Jawade Hafidz; Ngadino Ngadino (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
PLTU Batang is a steam power plant built in Batang Regency which is expected to meet the national electricity needs in the Java and Bali regions. The PLTU is located in three villages namely Ujungnegoro, Karanggeneng, and Ponowareng, near the Ujungnegoro Sea. Among the three villages, Karanggeneng had the biggest impact because the majority of its residents experienced the impact of the PLTU construction. The purpose of this study was to evaluate the influence of the PLTU development policy on the social life of the Karanggeneng Village community. This research uses the method juridical sociology, namely in this study the author conducts a review of the legal aspects to find out the applicable regulations, especially those relating to the role of notaries in land acquisition in. The data collection techniques used were interviews, observation, and documentation. The results showed that the existence of PLTU Batang affected the Karanggeneng Village community who were forced to sell their land, the future of the local community was also affected because of the change in land functions resulting in the community losing their livelihoods. The PLTU policy has an impact on current and future conditions, namely increasing unemployment and poverty in Karanggeneng Village, but the form of PT PBI's responsibility is the establishment of a KUB for affected communities, it is suggested that the construction of PLTU Batang should pay more attention to the socio-economic conditions of the community. This study aims to determine the process of land or land acquisition for PLTU development in Batang Regency, where there is a notary's role in making authentic deeds. The Land Acquisition Committee (P2T), refers to the land acquisition regulations at that time. This type of research is sociological juridical. The Land Acquisition Committee changes the designation of the Regional Spatial Planning (RTRW), also provides compensation in the form of money in the release of land that does not have ownership rights based on the Basic Agrarian Law (UUPA) and Government Regulation Number 24 of 1997. Notaries make the Deed of Releasing Rights to Land and the Deed of Debt Recognition in the said land acquisition, while the land acquisition is on state land, so there is no relinquishment of land rights in the legal act.